Exaggerated Proinflammatory and Th1 Responses in the Absence of γ/δ T Cells after Infection with Listeria monocytogenes - Skeen, Marianne J. (American Society for Microbiology, 2001)
While γ/δ T cells are involved in host defense and immunopathology in a variety of infectious diseases, their precise role is not yet clearly defined. In the absence of γ/δ T cells, mice die after infection with a dose of Listeria monocytogenes that is not lethal in immunologically intact animals. Morbidity might result from insufficient levels of cytokines normally produced by γ/δ T cells or conversely from an excess of cytokines due to a lack of down-regulation of the inflammatory response in the absence of γ/δ T cells. Consistent with a regulatory role, we found that systemic levels of proinflammatory cytokines (interleukin-6 [IL-6], IL-12, and gamma interferon [IFN-γ]) were significantly higher in the absence of γ/δ T cells during the innate phase of the response. Using combinations of genetically altered and immunodepleted mice, we found evidence for γ/δ T-cell-mediated regulation of IFN-γ production by multiple cell types of both lymphoid and myeloid lineages. The antigen-specific α/β T-cell response that followed the exaggerated innate response was also increased in γ/δ T-cell-deficient mice. These findings are consistent with an emerging picture from a variety of immune response models of a critical role for γ/δ T cells in down-modulation of the immune response.